Systematic revision of the pocket gopher genus Orthogeomys. Issue 2 (26th February 2016) - Spradling, Theresa A.; Demastes, James W.; Hafner, David J.; Milbach, Paige L.; Cervantes, Fernando A.; Hafner, Mark S.
Abstract : Pocket gophers of the genus Orthogeomys show unusually high morphological and ecological diversity compared to other genera in the family Geomyidae. Whereas this diverse group once was divided into 3 genera (Merriam 1895 ), a revision by Russell (1968) recognized only Orthogeomys, with Merriam's original genera relegated to subgeneric status as Heterogeomys, Macrogeomys, and Orthogeomys . Recent studies have called into question the monophyly of Orthogeomys, as well as the validity of 4 currently recognized Orthogeomys species. To date, the taxonomic validity of only 1 of these species has been verified (Hafner et al. 2014 ). In this analysis, the first to include all 11 recognized species of the genus, we examine 3 mitochondrial and 2 nuclear gene sequences (4, 352 base pairs) and analyze cranial morphology to explore relationships within the genus. Our data support a taxonomic revision that restricts the genus Orthogeomys to a single species ( O. grandis ) and combines the subgenera Heterogeomys and Macrogeomys into the resurrected genus, Heterogeomys (7 species). In addition, 3 currently recognized species of Orthogeomys are synonymized as follows: O. cuniculus with O. grandis ; H. thaeleri with H. dariensis ; and H. matagalpae with H. cherriei . A synonymy and a key to the species of the genera Orthogeomys and Heterogeomys are provided. Las tuzas del género Orthogeomys muestran una diversidad morfológica y ecológica inusual en comparación con otros géneros de la familia Geomyidae. Aunque este diverso grupo fue alguna vez dividido en 3 géneros (Merriam 1895 ), la revisión de Russell (1968) reconoció solo a Orthogeomys, mientras que los géneros originales de Merriam fueron relegados a estatus subgenérico como Heterogeomys, Macrogeomys y Orthogeomys . Estudios recientes han cuestionado la monofilia de Orthogeomys, así como la validez de 4 de las especies actualmente reconocidas. A la fecha, la validez taxonómica de sólo una de estas especies ha sido verificada. En este análisis, el primero en incluir las 11 especies reconocidas en el género, examinamos secuencias de 3 genes mitocondriales y 2 nucleares y analizamos la morfología craneal para explorar las relaciones dentro del género. Nuestras 4, 352 pares de bases de secuencias de ADN apoyan una revisión taxonómica que retiene al género Orthogeomys (incluyendo sólo a O. grandis ) y combina los subgéneros Heterogeomys y Macrogeomys en un género recuperado, Heterogeomys (7 especies). Además, 3 especies de Orthogeomys actualmente reconocidas son sinonimizadas de la siguiente forma: O. cuniculus con O. grandis ; H. thaeleri con H. dariensis ; y H. matagalpae con H. cherriei . Se incluye sinonimia y una clave para las especies de los géneros Orthogeomys y Heterogeomys .